Histone modifications and nuclear architecture: a review - Bártová, Eva; Krejcí, Jana; Harnicarová, Andrea; Galiová, Gabriela; Kozubek, Stanislav (The journal of histochemistry and cytochemistry, 2008)
Epigenetic modifications, such as acetylation, phosphorylation, methylation, ubiquitination, and ADP ribosylation, of the highly conserved core histones, H2A, H2B, H3, and H4, influence the genetic potential of DNA. The enormous regulatory potential of histone modification is illustrated in the vast array of epigenetic markers found throughout the genome. More than the other types of histone modification, acetylation and methylation of specific lysine residues on N-terminal histone tails are fundamental for the formation of chromatin domains, such as euchromatin, and facultative and constitutive heterochromatin. In addition, the modification of histones can cause a region of chromatin to undergo nuclear compartmentalization and, as such, specific epigenetic markers are non-randomly distributed within interphase nuclei. In this review, we summarize the principles behind epigenetic compartmentalization and the functional consequences of chromatin arrangement within interphase nuclei.
Keywords: homolog proteinu s chromoboxem 5; lidé; lidské chromozomy X; Methylation; Acetylation; Histone Deacetylase Inhibitors; Interphase; Cell Nucleus; Chromobox Protein Homolog 5; Gene Expression; buněčné jádro; Chromatin; Humans; chromatin; Histones; histony; Chromosomal Proteins, Non-Histone; epigeneze genetická; zvířata; Epigenesis, Genetic; acetylace; Animals; exprese genu; Chromosomes, Human, X; metylace; chromozomální proteiny, nehistonové; interfáze; inhibitory histondeacetylas